OPTIMIZATION OF SCREENING AND CARE OF PREGNANT WOMEN WITH HPV-ASSOCIATED DISEASES - Amonova, Z.D.; Kattakhodzhaeva, M.Kh. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Human papillomavirus (HPV) is recognized as the main etiological factor of cervical intraepithelial neoplasia (CIN) and cervical cancer (CrC). Physiological immunosuppression accompanying pregnancy contributes to the persistence of infection, as well as accelerates the progression of neoplastic processes. This article examines modern strategies for HPV screening in pregnant women, including molecular diagnostics, oncoprotein assessment, and minimally invasive treatment methods. Clinical observation results, as well as evidence of the effectiveness of ultrasound cavitation in correcting CIN and reducing the risk of perinatal complications, are presented. A diagnostic and management algorithm adapted to the characteristics of the gestational period has been proposed.